Growth hormone treatment promotes remote hippocampal plasticity after experimental cortical stroke - Sanchez-Bezanilla, Sonia (2021)
Cognitive impairment is common after stroke, and disturbances in hippocampal function are often involved, even in remote non-hippocampal injuries. In terms of hippocampal function, growth hormone (GH) is known to affects plasticity and cognition. We aimed to investigate whether GH treatment after an experimental cortical stroke could enhance remote hippocampal plasticity and the hippocampal-dependent visual discrimination task. C57BL6 male mice were subjected to cortical photothrombotic stroke. Stroke mice were then treated with either saline or GH at 48 h after occlusion for 28 days. We assessed learning and memory using mouse touchscreen platform for the visual discrimination task. We also evaluated markers of neural progenitor cells, synaptic plasticity and cerebrovascular remodelling in the hippocampal formation. GH treatment significantly improved the performance on visual discrimination task after stroke. We observed a concomitant increased number of bromodeoxyuridine-positive cells in the dentate gyrus of the hippocampus. We also detected increased protein levels and density of doublecortin, a neuronal precursor cells marker, as well as glutamate receptor 1 (GLuR1), a synaptic marker. These findings provide further neurobiological evidence for how GH treatment could be used to promote hippocampal plasticity in a remote region from the initial cortical injury, and thus enhance cognitive recovery after stroke.